Review of the BPHTB Collection System in the Transfer of Land and or Building Rights according to Lamongan Regency Regulation No. 10 of 2023 concerning Regional Taxes - Muljono, Bambang Eko; Royani, Ahmad; Sri Widayanti, Nurul Mahmuda (Jurnal Independent, 2024)
ABSTRACT Land and Building Acquisition Fee (hereinafter abbreviated as BPHTB) according to Law No. 1 of 2022 in Article 1 paragraph (37) states "Land and Building Acquisition Fee, hereinafter abbreviated as BPHTB, is a tax on the acquisition of land and/or building rights". The BPHTB collection system is calculated and paid by the taxpayer himself, namely with the Self Assessment System. In Lamongan Regency, Article 16 paragraph (1) of Lamongan Regency Regulation Number 10 of 2023 concerning Regional Taxes and Regional Retributions explains that PPAT/Notary requests proof of BPHTB payment from taxpayers, indicating that there are characteristics of a self-assessment system where BPHTB tax must be paid by taxpayers. In the Lamongan Regency Regulation, BPHTB payments are made electronically. In practice, this system is still mixed with the official assessment system in terms of research and calculation of BPHTB owed and then the supervision process by the government/fiscus carried out by the Lamongan Regency Regional Revenue Agency. Bapenda supervises if there is a discrepancy in the calculation, a tax underpayment letter will be issued which must be paid by the taxpayer, so that the self-assessment system is not fully running. This study uses a normative legal research method (normative law). The normative legal research method is a scientific research procedure to find the truth based on the logic of legal science from its normative side. In this normative research, the analysis method used is a qualitative approach by collecting data and materials needed through literature studies either through books, articles, journals or internet media. The results of this study are the system in collecting BPHTB, namely the self-assessment system, which still has the involvement of the fiscus/government in the BPHTB payment process, namely the official assessment system.